Evaluation of the Strength and the Moisture Sensitivity of the HMA Mixture with RAP - Chafat, Osamah H.; Al-Humeidawi, Basim H.; Abed, Alaa H. (Al-Nahrain Journal for Engineering Sciences, 2025)
Moisture-induced damage in asphalt pavements, is defined by adhesive failure at the binder-aggregate interface and decreased mechanical integrity, severely reduce pavement durability. The research examines the mechanical properties and moisture sensitivity of hot mix asphalt (HMA) enhanced with styrene-butadiene-styrene (SBS) polymer and including reclaimed asphalt pavement (RAP). Laboratory assessments, including indirect tensile strength (ITS) and tensile strength ratio (TSR) tests, were performed on conventional HMA, SBS-modified HMA (4% SBS), and SBS-modified HMA contained 20% RAP. The results indicated that SBS modification significantly improved mechanical and moisture resistance properties, where unconditioned ITS specimens increased by 37.1% and TSR value enhanced by 13.5%. The incorporation of RAP decreased ITS value by about 21 % relative to pure SBS-modified HMA; nevertheless, the SBS+RAP combination still show higher ITS and TSR values than conventional HMA.